The role-play of identities by the mediation of Literature: a small step towards the huge leap of intercultural competence development in teacher training in Mozambique - Monteiro, Ana Catarina Mateus (2020)
Advocating that, in order to develop Intercultural Competence, it is essential that the students engage in critical self-awareness processes that allow them to properly express their identity as a means to gradually assume ethnorelative views and value cultural diversity, this study focuses on two activities aiming at promoting an intercultural reflection on identity by the mediation of literature.